Dissecting the potential role of calreticulin as a prognostic biomarker for invasive breast cancer - Mehdi, Sabaghpour Azarian Mohammad (2020)
Breast cancer is the most common cancer occurring in women and the second leading cause of death in women after lung cancer worldwide. In cancer studies, invasion is an essential hallmark that allows cells to metastasize and spread to other parts of the body. Therefore, the focus of cancer studies is increasingly on invasion and metastasis-related biomarkers to detect the progression of breast cancer. Calreticulin (CRT) is a multipurpose endoplasmic reticulum (ER) protein which has been proposed as a potential biomarker for breast cancer. The high level of CRT expression has been reported to correlate with the range of invasiveness in breast cancer patients. In addition, presence of the extracellular matrix and stroma in the tumorigenic environment significantly increase the invasive phenotype and malignancy of breast cancer. Hence, a three-dimensional (3D) co-culture system using Matrigel as extracellular matrix offers a significant advantage in developing an in vivo-like model. In the first part of this study, MCF-7, MDA-MB-231 and MCF-10A breast cell lines were co-cultured with MRC-5 fibroblast cell line in the ratio of 3:1 in a 3D culture system to recapitulate in vivo-like expression of Calreticulin, the protein of interest. Subsequently, in the second part of this study, gene expression profiling of CRT and CRT-related candidate metastasis genes were carried out in 3D co-cultured cells developed in the first step. Finally, the correlation between CRT and CRT-related candidate metastasis genes were identified through statistical analysis. The results on the characterization of the developed 3D co-cultured micro-tissues showed occasional foci of lumen-like morphology and standard neoplastic features in the 3D structure. Moreover, the expression level of calreticulin and its localization in the micro-tissue samples were detected through immunohistochemistry revealed a patchy pattern of micro-tissues with wide positive signals of cytoplasmic CRT as well as irregular positive-stained nuclei. It was found that the expression of CRT and CRT-related candidate metastasis genes were down-regulated in all 3D co-cultured samples, in which PCMT1 and ER-Alpha genes were found to be significantly downregulated (P <0.01) in invasive breast cancer cells. While this study was unable to completely recapitulate in vivo-like expression of the CRT protein in the 3D co-cultured model due to technical constraints, it can serve as a baseline from which future work can be built upon. Nevertheless, based on the gene expression study, CRT and CRT-related candidate metastasis genes are shown to be involved in the progression of invasive breast cancer cells. This study also found that the CRT gene expression is highly correlated with all CRT-related candidate metastasis genes obtained from the developed micro-tissues. To conclude, this study suggests that CRT and CRT-related candidate metastasis genes may potentially serve as prognostic biomarkers for invasive breast cancer.